Experimental study on the damage characteristics of sol-gel antireflection coatings on large-aperture optical components by in-situ plasma cleaning - Rongqi Shen; Yuhai Li; Zixu Wang; Laixi Sun; Xiaodong Yuan; Xiang Dong; Xia Xiang; Bo Li; Xujie Liu; Xueshi Xu; Tingting Wang; Qingshun Bai (Nuclear Fusion)
Low-pressure plasma cleaning technology is currently regarded as a highly promising method for the effective in-situ removal of surface contaminants from large-aperture optical components (LAOC) (⩾430 mm) in laser fusion facilities. After a long cleaning, irreversible damage can occur to the sol-gel antireflective (AR) coatings on the surface of the LAOCs. Hence, a study was conducted to analyze the surface damage characteristics of low-pressure plasma cleaning on optical components and implement in-situ plasma cleaning techniques in the laser fusion facility. Initially, the impact of organic contaminant levels on the performance of optical components was assessed by experiments. Subsequently, the correlation between plasma cleaning duration, transmittance, wavelength peak, and laser-induced damage threshold of sol-gel antireflection coating on the LAOCs was examined. Experimental findings from plasma cleaning trials revealed that prolonged plasma exposure had a cumulative detrimental influence on coating thickness and optical performance, gradually increasing surface pores. Ultimately, investigating the surface damage mechanism of sol-gel AR coatings during low-pressure plasma cleaning establishes a groundwork for achieving non-destructive in-situ cleaning of LAOCs in laser fusion facilities.